MANAJEMEN PENDIDIKAN TAMAN KANAK-KANAK ISLAM KOTA PADANGSIDIMPUAN - Rosmaimuna Siregar (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Researchers applying education management especially in the field of curriculum at Kindergarten of Islam in Padang sidimpuan city. Then made a comparison between the application of curriculum management in order to know the similarities and differences between the two models of kindergarten.To reach the goal, the researcher uses qualitative approach with natural background as the source of data. To collect the necessary data in accordance with the question focus and research objectives, the researcher uses observation, interview and document review techniques. Further data obtained were analyzed by interactive analysis model.The findings of researchers directly related to the management functions are in each kindergarten. Starting from curriculum planning, pengorgaanisasian, implementation, and supervision of the curriculum. The equation found is mostly in the planning of the curriculum, because each kindergarten has a curriculum planning reference issued by the agency and the depag. Likewise with the supervision of both done by the school as well as the city education office and department of Religious city of Padangsidimpuan. The difference lies in curriculum development, which has directly distinguished the organizing and implementation of the curriculum.If associated with the opinion of Islamic education management experts then Kindergarten Al-Quran is categorized as RA because early childhood education is formally and under the auspices of religious ministries named with RA, while the TK Islam Terpadu and Islamic organizations. Thus the Islamic Kindergarten in the city of Padangsidimpuan must apply the principles of management manipulated by public schools characterized by Islam, because it is under the auspices of the curriculum education office.This research is practically expected to open a new understanding for the head of kindergarten, especially about urgency of Islamic education management known and applied in every educational activity. So that managed education really applies the principles of education that have been studied and studied by Islamic education management experts.